Antimicrobial resistance and associated genetic background of Histophilus somni isolated from clinically affected and healthy cattle - Ueno, Yuichi; Suzuki, Kenta; Takamura, Yuji; Hoshinoo, Kaori; Takamatsu, Daisuke; Katsuda, Ken (Frontiers in Veterinary Science, 2022)
Histophilus somni, a member of the Pasteurellaceae family, causes various diseases, including thrombotic meningoencephalitis and respiratory diseases. Here, 166 isolates recovered from Japanese cattle with various diseases between the late 1970s and the 2010s were subjected to susceptibility testing against 14 antimicrobials (ampicillin, amoxicillin, cefazolin, ceftiofur, kanamycin, streptomycin, nalidixic acid, enrofloxacin, danofloxacin, florfenicol, erythromycin, tylosin, oxytetracycline, and fosfomycin). The proportions of antimicrobial-resistant/intermediate isolates were low in the total isolates, with resistance rates ranging from 0% for ceftiofur and florfenicol to 13.2% for ampicillin. However, relatively high minimum inhibitory concentrations (MICs) and resistance/intermediate rates were observed in the isolates from cattle with respiratory diseases; i.e., 21/53 isolates (39.6%) showed resistance or intermediate to one or more antimicrobials for treatment of respiratory diseases, and the resistance/intermediate rates to oxytetracycline, kanamycin, ampicillin, amoxicillin, nalidixic acid, and danofloxacin were 28.3, 24.5, 24.5, 13.2, 1.9, and 1.9%, respectively. Isolates with high MICs tended to possess antimicrobial resistance genes, which may confer antimicrobial resistance phenotypes. In particular, all isolates with MICs of ampicillin/amoxicillin, kanamycin, and oxytetracycline ≥2 μg/mL, ≥512 μg/mL, and ≥4 μg/mL possessed blaROB − 1, aphA-1, and tetH/tetR, respectively, whereas isolates whose MICs were lower than the above-mentioned values did not possess these resistance genes. These results suggest that the resistance genes detected in this study are primarily responsible for the reduced susceptibility of H. somni strains to these antimicrobials. As integrative and conjugative element (ICEs)-associated genes were detected only in genetically related isolates possessing antimicrobial resistance genes, ICEs may play an important role in the spread of resistance genes in some genetic groups of H. somni strains.